Characteristics of optical glass plate refractive index sensor based on surface plasmon resonance. Issue 12 (December 2014) - Tang, Cien‐Jen; Lin, Chen‐Hung; Hsiao, Li‐Jen; Chen, Wei‐Tsung; Jaing, Cheng‐Chung; Lin, Hoang Yan
ABSTRACT This work presents a novel refractive index sensor structure based on surface plasmon resonance, consisting of planar glass plates coated with multilayer thin film. The glass plate guides the light, the multilayer metallic thin film excites the surface plasmon wave, and the dielectric film is used to fine tune the resonance wavelength. The resolution and spectrum variation and the wavelength shift, for aqueous solutions of salt of various concentrations, are measured. The sensor resolution and sensitivity is obtained. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:3009–3012, 2014